Potentiostatic Electrodeposition of FeCo Thin Films: Influence of Deposition Temperature and Saccharin Concentration - Ayuningsih Arum (Chemistry and Materials, 2025)
The FeCo thin films were synthesized using a potentiostatic electrodeposition technique under varying deposition temperatures and saccharin compositions. The effects of these parameters on the film’s crystallinity, composition, microstructure, and deposition behavior were systematically investigated. X-ray diffraction confirmed the formation of a single-phase FeCo structure under all conditions. Increasing the deposition temperature enhanced mass transfer and reduced anomalous codeposition behavior, as evidenced by the compositional shift toward higher cobalt content. The presence of saccharin was found to significantly influence the nucleation and growth processes through adsorption and the formation of metal–saccharinate complexes, which altered the deposition behavior. These results demonstrate that optimizing deposition parameters enables precise control over the composition and structure of FeCo thin films, which is crucial for the functional applications of magnetic and electrocatalysis.